2021
DOI: 10.2807/1560-7917.es.2021.26.29.2001600
|View full text |Cite
|
Sign up to set email alerts
|

Decline of influenza and respiratory syncytial virus detection in facility-based surveillance during the COVID-19 pandemic, South Africa, January to October 2020

Abstract: Background In South Africa, COVID-19 control measures to prevent SARS-CoV-2 spread were initiated on 16 March 2020. Such measures may also impact the spread of other pathogens, including influenza virus and respiratory syncytial virus (RSV) with implications for future annual epidemics and expectations for the subsequent northern hemisphere winter. Methods We assessed the detection of influenza and RSV through facility-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 14 publications
(22 reference statements)
8
119
2
3
Order By: Relevance
“…Reports from other countries, including China, Australia, and France, also cited diminished flu cases since the pandemic was declared [ 26 , 27 ]. Stamm et al described a parallel decline in flu and RSV incidence in Germany in 2020, while Tempia et al reported a similar trend in South Africa [ 28 , 29 ]. Likewise, both flu and RSV cases declined in the USA in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from other countries, including China, Australia, and France, also cited diminished flu cases since the pandemic was declared [ 26 , 27 ]. Stamm et al described a parallel decline in flu and RSV incidence in Germany in 2020, while Tempia et al reported a similar trend in South Africa [ 28 , 29 ]. Likewise, both flu and RSV cases declined in the USA in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of an epidemiologic integrated approach has to be highlighted whereas the widest use of non-pharmaceutical interventions (NPIs) during the current COVID-19 pandemic has changed the epidemiologic scenario of influenza and other respiratory viruses [58,59], with a decline of influenza and hRSV detection followed by a resurgence of hRSV incidence in hospitalised children after the relaxation of public health measures [60,61]. Therefore, the importance of molecular epidemiology, in support of the surveillance systems in place against respiratory pathogens both in community and hospital settings, must be emphasised also in the light of a changing and more complex global public health scenario and of the increasing need to update vaccination strategies [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, a facility-based surveillance revealed a decline in RSV and influenza virus detection with strengthening of the most stringent COVID-19 control strategies, compared with previous years. However, a subsequent increase in RSV was observed after the typical season, possibly reflecting the easing of measures [58]. Indeed, further cost analysis studies would document a proportional drop in related medical costs in terms of billions of euros/dollars in those countries registering a drastic reduction in RSV hospitalization (up to 70-90%) during the containment measures following COVID-19.…”
Section: Impact Of Covid-19 Containment Measures On Bronchiolitismentioning
confidence: 96%
“…In South Africa, a facility-based surveillance revealed a decline in RSV and influenza virus detection with strengthening of the most stringent COVID-19 control strategies, compared with previous years. However, a subsequent increase in RSV was observed after the typical season, possibly reflecting the easing of measures [ 58 ].…”
Section: Impact Of Covid-19 Containment Measures On Bronchiolitismentioning
confidence: 99%